2011
DOI: 10.4103/0971-9261.74521
|View full text |Cite
|
Sign up to set email alerts
|

Perforation into gut by ventriculoperitoneal shunts: A report of two cases and review of the literature

Abstract: We report two cases of gastrointestinal perforation by ventriculoperitoneal (VP) shunts and review the literature on the topic. The time interval between shunt surgery and detection of bowel perforation is minimum in infants and increases with age. Sigmoid and transverse colon followed by stomach are the most frequent sites of gastrointestinal perforations by VP shunts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 16 publications
0
31
0
Order By: Relevance
“…The peritoneal end of the VP shunt has been associated with complications such as mechanical blockade by omentum leading to shunt failure, pseudocyst formation, intestinal volvulus, inguinal hernia, perforations of hollow viscus, penetration into solid organs & abdominal wall and protrusion outside body [2].…”
Section: Discussionmentioning
confidence: 99%
“…The peritoneal end of the VP shunt has been associated with complications such as mechanical blockade by omentum leading to shunt failure, pseudocyst formation, intestinal volvulus, inguinal hernia, perforations of hollow viscus, penetration into solid organs & abdominal wall and protrusion outside body [2].…”
Section: Discussionmentioning
confidence: 99%
“…In a recently published review by Hai et al [11], anal protrusions of distal shunt catheters were reported in 96 patients. Since that time, 15 cases have been reported [7,8,[12][13][14][15][16][17][18][19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Because the bowel perforation caused by the shunt is usually very small, in most of the cases, it would seals by itself. Thus, laparotomy is rarely necessary and is indicated only for those patients who present with acute abdomen [11,29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis is obvious when anal or oral protrusion of the catheter occurs, but some situations should raise the suspicion of this complication, namely ventriculitis or meningitis due to an "unusual" enteric organism, such gram-negative or anaerobic, or a CT scan showing pneumocephalus without another cause [3,7] . This patient had 2 episodes of acute meningitis due to E. coli a very long time after VPS placement (28 years).…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of a VPS perforating the bowel must be individualized, taking into account the clinical presentation [3,4,7,8] . Three principles are important: external drainage of the proximal part until the cerebrospinal fluid is biochemically near-normal and sterile on culture, intravenous antibiotics, and removal of the perforating part of the catheter [2,3] .…”
Section: Discussionmentioning
confidence: 99%